Android based applications for embedded system - Ablaissov, Daniyar (2012)
This project first involves the studying and familiarization of the Zoom™ OMAP35x Development Kit, which is a product-ready hardware and software development platform suitable for embedded applications. An Android Operating System developed for the board is then installed. Applications compatible with Android OS then developed in order to explore the various development techniques for Android based embedded system.